A First Assessment of SARS-CoV-2 Circulation in Bats of Central–Southern Italy - Hiba Dakroub; Danilo Russo; Luca Cistrone; Francesco Serra; Giovanna Fusco; Esterina De Carlo; Maria Grazia Amoroso (Pathogens, 2022)
One serious concern associated with the SARS-CoV-2 pandemic is that the virus might spill back from humans to wildlife, which would render some animal species reservoirs of the human virus. We assessed the potential circulation of SARS-CoV-2 caused by reverse infection from humans to bats, by performing bat surveillance from different sites in Central–Southern Italy. We restricted our survey to sampling techniques that are minimally invasive and can therefore be broadly applied by non-medical operators such as bat workers. We collected 240 droppings or saliva from 129 bats and tested them using specific and general primers for SARS-CoV-2 and coronaviruses, respectively. All samples (127 nasal swabs and 113 faecal droppings) were negative for SARS-CoV-2, and these results were confirmed by testing the samples with the Droplet Digital PCR. Additionally, pancoronavirus end-point RT-PCR was performed, and no sample showed specific bands. This outcome is a first step towards a better understanding of the reverse transmission of this virus to bats. Although the occurrence of a reverse zoonotic pattern can only be fully established by serological testing, the latter might represent an in-depth follow-up to a broad-scale preliminary assessment performed with our approach. We encourage the systematic surveillance of bats to help prevent reverse zoonotic episodes that would jeopardize human health, as well as biodiversity conservation and management.